Utilization of Palm Oil Sludge for Poultry Feed - Sinurat, Arnold P (Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
Indonesia imports feedstuffs such as corn and soybean meal to fulfill the requirement in the country. The volume of imports is increasing due to the increasing demand on livestock products. On the other hand, we have a huge amount of unconventional feedstuffs produced locally. Palm oil sludge is one of the unconventional feedstuffs that have not been utilized. The palm oil sludge production in 2001 was approximately 632,570 ton and is increasing following the increasing of palm oil productions in Indonesia. Some reports have shown that palm oil sludge could be included in the feed of cattle, sheep, pigs and poultry. The sludge is limited in use for poultry feed due to high fiber contents and low nutrient digestibility. Indonesian Research Institute for Animal Production conducted researches in order to improve nutritive values of palm oil sludge by fermentation method. The fermentation increased the protein, amino acids, metabolisable energy (TME) and reduced the fiber contents of the sludge. Feeding trials showed that the fermented products could be included as much as 10% in diets of broilers and native chickens, but 15% could be included in diet of growing ducks. Â  Key words: Palm oil sludge, nutritive values, poultry feed, fermentation